Corporate reputation risk in relation to the social media landscape - Rensburg, Ronel S. (University of Pretoria, 2018)
Organisations are vulnerable in terms of the potential reputation damage social media can cause. Social media provide a voice to all, whether it be based on fact or fiction. A low tolerance for corporate wrongdoing (however minor), deep-rooted anti-corporate sentiments and the demand for compliance with the triple context philosophy fuel social media conversations about brands. Potentially damaging reputation incidents often grow to full-blown crises due to the intensity, reach and immediacy of social media. Thus the ultimate question organisations face is how they should manage this specific management dilemma. This study followed the interpretive qualitative approach in a comparative case study. Four South African organisations from the tertiary (services) sector participated in the study. Three executives in each organisation (communication/marketing, risk management and social media specialists) participated in interviews. A number of secondary sources (organisational and archival documents) were also included in each case study. The empirical results and literature suggest that organisations need a multi-pronged approach to navigate this management dilemma. The first leg is Enterprise Risk Management (ERM), which should be grounded in corporate strategy and encompass the entire organisation. The interconnectedness of risks and organisational dynamics confirm that linear thinking would not address problems adequately. Establishing a risk culture in organisations is pivotal and would enable the implementation of ERM. All employees, not just the board or executive managers, ought to feel compelled to report and manage risks according to specific policies and procedures. They need to understand their potential contribution to shielding their organisation from damaging factors. The second leg is purposeful corporate reputation management. This approach is deliberate and ought to guide the corporate communication strategy. While a chief executive officer or board carry the ultimate symbolic responsibility for corporate reputation, all employees ought to understand their roles in a reputation culture, with the emphasis on avoiding reputation damage. Training employees regarding corporate reputation and appropriate social media behaviour are valued within most organisations. The final leg pertains to understanding crisis management in the broadest sense and social media crises in particular. Preventing issues from escalating into crises is the ideal. Managing an organisation’s reactions to such incidents One participating organisation illustrated the need for carefully weighed responses when it incurred a boycott campaign when a specific population segment. This thesis further considers the notion of a management framework to deal with reputation risk in relation to the social media landscape. Organisations agree that the fluidity of social media and society make such a notion futile. However, they agree on a number of key principles such as executive level knowledge of and involvement, well-established response procedures and adequately equipped teams of specialists. The original contribution of this thesis lie in both the propositions in relation to each of the objectives and the suggested framework for the management of corporate reputation risk in relation to the social media landscape.